Endocranial morphology of the Brazilian Permian dicynodont Rastodon procurvidens (Therapsida: Anomodontia) - de Simão‐Oliveira, Daniel (J Anat, 2019)
Dicynodontia is a major clade of terrestrial tetrapods that greatly diversified during the Permian and Triassic periods, reaching a worldwide distribution. In this study, the endocranial cavity of the Brazilian Permian dicynodont Rastodon procurvidens is described based on a digital endocast obtained using digital imaging (X‐ray computed tomography) and 3D modeling. It was possible to reconstruct the brain, olfactory bulbs, inner ear, some neurovascular canals, cranial nerves, the nasal cavity, and the maxillary recesses. The endocast of R. procurvidens preserves a typical plesiomorphic morphology of non‐mammaliaform therapsids, being predominantly tubular and displaying a relatively short and robust hindbrain. Encephalization quotients (EQs) were calculated for R. procurvidens, resulting in EQs of 0.09 ± 0.03 and 0.13 ± 0.05 (Jerison’s EQ and Manger’s EQ, respectively). Finally, some biological implications of the endocast morphology were inferred for R. procurvidens. Its inner ear is especially small, and its orientation implies a slightly downturned head posture in life. Furthermore, the presence of uncompressed maxillary recesses in R. procurvidens indicates a correlation between the enlargement of the recesses and the reduction of the tusks, also seen in other dicynodonts with reduced tusks.